Efeito de ambientes contrastantes na produção florestal e nas propriedades da madeira de clones de Eucalyptus - Rodrigues, Brunela Pollastrelli (2017)
The genus Eucalyptus has different species known by its plasticity, species that can adapt to diverse edaphoclimatic conditions. Nevertheless, this fact does not guarantee that species planted with the different condition will present the same anatomical, physical and chemical proprieties and thereafter it will produce wood on an equal amount and desired quality to a specific purpose. The changes that occurred during the wood formation, caused by adverse growth condition creates a huge difficult to predict the productive behavior and technological of the wood. Despite the many research with the eucalyptus’ wood proprieties, a little is known about the influence of contrasting growth environments on the formation and properties of wood from Eucalyptus clones. Based on this, this study aimed to evaluate the effect of contrasting environments on the productivity and proprieties of eucalyptus wood clones. The trees used in this study were collected at Montezuma, a city located in the north of Minas Gerais State (938m altitude and 570mm rainfall) and in Nova Almeida, Serra, located on the coast of the Espirito Santo State (90m altitude and 1267mm as average rainfall). Five trees from each clone were sampled at each study site, totaling 200 trees 100 of each locality). From them was obtained the following measures: diameter, Diameter at Breast Height – DBH (1,30m from the soil), height and volume, the Mean Annual Increment – MAI was calculated and was the bark percentage. From each tree, were collected three discs at the DAP height to the propriety studies. The basic density, wood anatomy and the wood chemistry.The experiment was conducted in a completely randomized design (CRD). A T- Student test was performed to verify the difference of the variables means values between the two studied localities. To verify the existence of an interaction event between the clones and local on the studied variables, an ANOVA was performed using the F Test (p = 0,05). To the variables that were verified the interaction, the stability and adaptability of clones were performed using the Selegen software. There was significant interaction between genotypes and environments at 5% significance for all study variables.There was a significant interaction between genotypes and environments at 5% significance for all variables of this study. The wood produced in Nova Almeida - ES, the place with the highest rainfall and the lowest thermal amplitude, presented the highest production in wood and the most desirable anatomical and chemical properties for the production of cellulosic pulp. The wood produced in Montezuma – MG, site with higher temperature range and annual water deficit, showed higher values for density, extractives, lignin, vessel diameter, vessel frequency and thickness of fiber wall. About the stability and adaptability analysis, it was possible to select some clones with adaptability and stability simultaneously in the two studied sites, indicating that the possible selection of stable clones.This study allowed a better understanding of the production and properties of wood in response to contrasting growth sites, assisting in the targeting and selection of groups of clones better adapted and with greater plasticity for different environmental conditions.